The Mentalized Affectivity Scale (MAS): Development and validation of the Italian version. - Teresa Rinaldi; Ilaria Castelli; Andrea Greco; David M Greenberg; Elliot Jurist; Annalisa Valle; Antonella Marchetti (PLoS ONE)
This study proposes a psychometric validation of the Italian version of the Mentalized Affectivity Scale (MAS) developed by Greenberg and colleagues in 2017. The mentalized affectivity construct integrates mentalization ability in the process of emotional regulation. An adult sample (N = 506) completed the 60-items MAS online version. In contrast to the three-factor structure of the original version, the Italian context confirmatory and exploratory factor analyses with splitted sample (CFA = 258; EFA = 248) revealed a five-factor structure. The hierarchically structured MAS factors are: Emotional Processing (being able to process emotion in situations); Expressing Emotions (talking and knowing emotions); Identifying Emotions (awareness of emotions); Control Processing (to control emotional reactions and expression), and Autobiographical Memory (related to childhood experiences). We also verified the convergent validity and reliability of the Italian version of the MAS by correlating the above five factors with measures of emotion regulation and reflective functioning. Moreover, we analyzed the relationships among the factors of the MAS, personality measures and well-being indexes, such as life satisfaction and self-efficacy: The new 35-item MAS scale showed robust correlations with all the tested constructs. Our results confirm that the MAS is a useful measure to assess mentalized affectivity, with the Italian version showing a more complex structure than the original English one, thus enriching the literature about mentalization.